Determination of (+)-Catechin and Antioxidant Activity in Faloak (Sterculia quadrifida R. Br) Stem Bark Infusion - Audrey Gracelia Riwu; Jusak Nugraha; Djoko Agus Purwanto; Erwin Astha Triyono (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Oxidative stress is a condition that can damage human cells and tissues and has been linked to a number of illnesses, including cancer, cardiovascular disease, autoimmune disorders, and neurological diseases. Oxidative stress conditions can be brought on by pollution, radiation exposure, and an unhealthy lifestyle. Antioxidants are substances that can be used to both prevent and treat oxidative stress. This study aimed to identify and quantify (+)-catechin levels and antioxidant activity of the stem bark of Sterculia quadrifida R. Br extracted by the infusion method, a method similar to traditional medicine processing generally in the community. Determination of (+)-catechin and antioxidant activity of S. quadrifida were evaluated by HPLC and DPPH assay, respectively. Quantification of (+) catechin content by HPLC system with wavelength 280 nm and antioxidant activity by spectrophotometry method with wavelength 517 nm. The results show that the mean value of (+)-catechin level was 7.786% and the IC50 value of the antioxidant activity was 51.5 ug/mL having a moderate antioxidant activity category. S. quadrifida stem bark infusion can be utilized as a medication candidate for the prevention or treatment of a variety of disorders caused by oxidative stress.